Suppression of Proinflammatory Cytokines by Etlingera alba (A.D.) Poulsen Rhizome Extract and Its Antibacterial Properties - Rini Hamsidi; Wahyuni Wahyuni; Idin Sahidin; Evi Apriyani; Harsono Harsono; Nur Arsianti Azizah; Fadhliyah Malik; Agung Wibawa Mahatva Yodha; La Ode Muhammad Julian Purnama; Adryan Fristiohady (Hindawi Limited, 2021)
Etlingera alba is one of the Etlingera plants that has not been studied intensively. Plants that belong to the same genus have similar constituents and pharmacological activities. Thus, we aim to investigate the chemical composition and pharmacological activities, namely, anti-inflammatory and antibacterial properties, of E. alba rhizome extract (EA). The chemical constituent was detected using the test tube method. The inflammatory model rats were obtained by inducing them with 1% carrageenan, and their palm edema volume and cytokine levels, namely, IL-6, IL-12, and TNF-α, were measured. Antibacterial activity was performed with broth microdilution. The phytochemical screening of EA was detecting alkaloids, flavonoids, tannins, steroids, and phenols. The EA has anti-inflammatory activity by reducing the palms' edema volume and cytokine levels (IL-6, IL-12, and TNF-α), and the optimal concentration was 400 mg/kg body weight (BW). On the other hand, EA also exhibited antibacterial properties against E. coli and S. enterica. In conclusion, similar to other Etlingera plants, EA also demonstrates pharmacological activities, namely, anti-inflammatory and antibacterial properties.